Different Drifters: Disability and Illness in Contemporary U.S. Road Films - Induráin Eraso, Carmen (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
The main aim of this article is to trace historically the representation of illness in the US American road movie exploring how the presence of different, diseased bodies may shatter generic expectations and subsequently result in the genre’s revitalization. After exploring the factors accounting for the increasing representation of sick people in the contemporary road movie, a sample of representative road films (The Straight Story, Around the Bend, The Living End, Boys on the Side, My Own Private Idaho, Homer & Eddie and Rain Man) is analysed to understand the contribution of ill drifters during the 1990-2010 period. This contribution mainly focuses upon the increasing, though not always positive, visibility of this underrepresented minority in this genre and evidences how illness and impairment may throw social outcasts on a drifting journey. Since the 1990s the road genre is fighting against the discrimination of contemporary US society against ill people on the big screen. In doing so, it offers a potentially wider and more positive viewer identification and a more democratic social representation and, at the same time, shows a significant revitalization as a genre.